Variations in Infant CYP2B6 Genotype Associated with the Need for Pharmacological Treatment for Neonatal Abstinence Syndrome in Infants of Methadone-Maintained Opioid-Dependent Mothers - Mactier, Helen; McLaughlin, Poppy; Gillis, Cheryl; Osselton, Michael David (American Journal of Perinatology, 2017)
Background Neonatal abstinence syndrome (NAS) in infants of methadone-maintained opioid-dependent (MMOD) mothers cannot be predicted in individual cases. We investigated whether variation in infant genotype is associated with severity of NAS.Methods This is a pilot observational cohort study of 21 MMOD mothers and their newborns. Infant buccal swabs were obtained soon after delivery, together with a maternal blood sample for the determination of maternal plasma methadone concentration. Genomic variation in five opioid-related genes (ABCB1, COMT, CYP2B6, CYP2D6, and OPRM1) was ascertained from infant buccal swabs and related to need for pharmacological treatment of NAS.Results Out of 21 infants, 11 (52%) required treatment for NAS. Mothers of treated infants tended to have been prescribed higher doses of methadone, but plasma methadone concentrations did not differ between mothers of treated or untreated babies. Treated and untreated babies did not differ in terms of method of feeding. Treated infants were more likely to carry the normal (homozygous) allele at 516 and 785 regions of CYP2B6 gene (p = 0.015 and 0.023, respectively). There were no differences in any other genes between infants who did or did not require treatment for NAS.Conclusion Genomic variation in CYP2B6 may explain, at least in part, severity of NAS.
Keywords: neonatal abstinence syndrome; newborn; methadone; genotype